2011
DOI: 10.1371/journal.pone.0017615
|View full text |Cite
|
Sign up to set email alerts
|

The Cyanobacterial Hepatotoxin Microcystin Binds to Proteins and Increases the Fitness of Microcystis under Oxidative Stress Conditions

Abstract: Microcystins are cyanobacterial toxins that represent a serious threat to drinking water and recreational lakes worldwide. Here, we show that microcystin fulfils an important function within cells of its natural producer Microcystis. The microcystin deficient mutant ΔmcyB showed significant changes in the accumulation of proteins, including several enzymes of the Calvin cycle, phycobiliproteins and two NADPH-dependent reductases. We have discovered that microcystin binds to a number of these proteins in vivo a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
347
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 365 publications
(378 citation statements)
references
References 36 publications
(49 reference statements)
12
347
2
2
Order By: Relevance
“…They found that the toxic Microcystis strain NIVA-CYA 140 displaced the non-toxic strain NIVA-CYA 43 ( ¼ PCC 7005) at low CO 2 conditions, whereas the outcome of competition was reversed at high CO 2 conditions. On the basis of additional experiments with Microcystis PCC 7806 and its non-MC-producing mutant, Van de Waal et al explained their results by differences in MC production between the strains, implicating that MCs might have a role in carbon assimilation (see also Zilliges et al, 2011). However, in our study, we did not find an association between C i uptake genotypes and MC genes.…”
Section: Growth Under Different C I Conditionscontrasting
confidence: 55%
“…They found that the toxic Microcystis strain NIVA-CYA 140 displaced the non-toxic strain NIVA-CYA 43 ( ¼ PCC 7005) at low CO 2 conditions, whereas the outcome of competition was reversed at high CO 2 conditions. On the basis of additional experiments with Microcystis PCC 7806 and its non-MC-producing mutant, Van de Waal et al explained their results by differences in MC production between the strains, implicating that MCs might have a role in carbon assimilation (see also Zilliges et al, 2011). However, in our study, we did not find an association between C i uptake genotypes and MC genes.…”
Section: Growth Under Different C I Conditionscontrasting
confidence: 55%
“…Further studies may help to confirm this putative role of MC in the cellular metabolism and to partially elucidate the toxin dynamic observed in the field. On the other hand, recent studies have also shown that a large fraction of MCs are covalently bonded to proteins within Microcystis cells and cannot be extracted using methanol (Zilliges et al, 2011;Meissner et al, 2013Meissner et al, , 2014. Thus, the lower total MC could indicate a higher fraction of bound MC at higher temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…By using high temperature conditions and inducing oxidative stress, the researchers observed a specific and covalent interaction of MC with several proteins, resulting in their accumulation, suggesting another possible function of this metabolite. Recently, Zilliges et al (2011) proposed that MCs can bind to some phycobilins and thus protect them from degradation by reactive oxygen species. The apparent loss of MC is likely the consequence of a specific and covalent binding of the toxin to various proteins (Meissner et al, 2013(Meissner et al, , 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Positive properties are (1) HP acts very fast, and a lake is safe for swimming (or other interrupted functionality) again after 3 days only; (2) good sustainability, no lasting chemical traces of the added HP, nor toxic substances including released cyanotoxins or particulate organic matter from dead cyanobacteria are retained in the water body (note: this statement is based on current knowledge from lake studies in the Netherlands; however, it may not hold true for each and every case, appropriate controls on toxin release and persistence should always be part of any treatment programme); (3) damage to other phyto-and zooplankton species is none or limited, and HP at the recommended maximal cyanocidal concentration of 5 mg L -1 is also safe for macrofauna, fishes and aquatic plants; (4) affordable costs. A range of questions has been formulated that still need to be answered, including effects of HP on other prokaryotes in the lake ecosystem and potential adverse effects on nutrient cycles, as well as possibilities that some cyanobacterial strains may prove resistant after all and will conquer the lake ecosystem (Dziallas and Grossart 2011;Zilliges et al 2011). Most of all, it is stressed that for now the HP-based peroxide method for lake mitigation establishes a tool for suppression of cyanobacteria.…”
Section: Considerations About Hp Applicationmentioning
confidence: 99%